Hepatitis C virus NS5A and core proteins regulate epithelial-mesenchymal transition biomarkers in hepatoma cells - TG Heredia-Torres; SA Lozano-Sepúlveda; AR Rincón-Sánchez; AMG Rivas-Estilla (Annals of Hepatology, 2022)
Introduction and Objectives: Hepatitis C virus (HCV) NS5A and Core proteins play a key role in carcinogenesis development. Epithelial-mesenchymal transition (EMT) induced by HCV has been related to Snail and TGFβ1 upregulation and E-cadherin downregulation. This study aimed to evaluate the effect of HCV NS5A and Core proteins in the regulation of Snail, TGFβ1 and E-cadherin by transient transfection in the hepatoma cell system. Materials and Methodology: Huh 7 cells were transfected with an empty vector, and 0.5 - 1.0μg of pNluc-NS5A-HCV or pCore-HCV plasmids for 24 - 48h and then proteins and RNA were extracted. NS5A protein expression was measured by NanoLuc activity. Core, Snail, TGFβ1 and E-cadherin protein levels were evaluated by Western Blot. NS5A and Core transcripts were quantified by RT-qPCR. Relative expression of SNAI, TGFβ1 and CDH1 was calculated in relation to ACTB and GAPDH endogenous expression. Results: Viral NS5A and Core proteins were expressed in transfected Huh 7 cells. Transient transfection with pNluc-NS5A-HCV upregulated snail expression (4-fold) but downregulated E-cadherin expression (0.6-fold) at 24h. In addition, upregulated TGFβ1 expression (4-fold) and downregulates E-cadherin expression (0.7-fold) at 48h compared to the control. Meanwhile, transfection of pCore-HCV for 24h upregulated snail expression (2-fold); in contrast, it downregulated E-cadherin expression (0.3-fold) compared to control at 48h. Discussion: Snail and TGFβ1 upregulation and E-cadherin downregulation had been associated with HCV infection in other studies. Our results suggest that HCV NS5A and Core have a direct role in EMT. Conclusion: Hepatitis C virus regulates epithelial-mesenchymal transition biomarkers by NS5A and Core proteins expression in hepatoma cells. Funding: The resources used in this study were from the hospital without any additional financing Declaration of interest: The authors declare no potential conflicts of interest.